A novel software-radio-defined passive RFID reading system with real-time collision resolution. (11th November 2011) - Sun, Yuan; Hawrylak, Peter J.; Mao, Zhi-Hong; Mickle, Marlin H.
The ISO 18000-6C standard defines the air interface of UHF passive RFID tags. According to the timing specification in this standard, a conforming interrogator (or reader) shall complete the inventory round for tags in a soft real time. This research develops a software-defined radio reconfigurable FPGA-based interrogator for the standard to address the stringent time constraints of the tag-reader handshakes. This flexible interrogator is fully customisable and can be utilised for typical applications including standard conformance test automation and large-scale programming for tag groups. Furthermore, on-chip signal processing allows for real-time online collision resolution in a tag-intensive environment and can significantly improve the system reading efficiency.